Who is going to save the final girl? the politics of representation in the films halloween and the silence of the lambs - Boer, Raphael Albuquerque de (2014)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro de Comunicação e Expressão, Programa de Pós-Graduação em Inglês: Estudos Linguísticos e Literários, Florianópolis, 2014